Children and female employment in Mongolia - Elena Nikolova; Jakub Polansky (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2022)
Although a large body of literature has argued that motherhood has a profound and longlasting negative effect on the employment and earnings of women, there is little evidence focusing on the post-communist region. This paper exploits the latest round of the EBRDWorld Bank Life in Transition Survey (LiTS) and of the Mongolian National Statistics Office Household Socio-Economic Survey (HSES) to examine the correlation between the presence of children of different age categories in a family and female employment in Mongolia in 2016. We examine the availability of childcare, social norms and attitudes towards women, as well as household decision-making as potential explanations. We find that small children decrease the probability of female employment relative to women with no small children. In particular, women with two children aged one to six years are 21.5 percentage points less likely to be employed. Our results also suggest that cultural biases against women may be - at least partially - responsible for the low female employment levels which we uncovered. These results are unlikely to be driven by omitted variable bias.
Keywords: J16; J13; J20; 330; children; female employment; Mongolia; women